Complex sympathetic regulation in adolescent mitral valve prolapse - Bona Olexova, L; Visnovcova, Z; Ferencova, N; Jurko, A; Tonhajzerova, I (Physiological research, 2021)
Mitral valve prolapse (MVP) belongs to cardiac disorders characterized by impaired closure of mitral leaflets. We studied adolescent group of patients with MVP suffering from symptomatology that cannot be explained by mitral regurgitation alone. Several studies suggested that symptoms can be explained by autonomic, in particular sympathetic-linked dysfunction. Thus, we assessed non-invasive sympathetic indices of blood pressure and heart rate variability and electrodermal activity (EDA). Fifty-three adolescents with MVP (age: 15.1+/-0.4 years) and 43 healthy age- and gender-matched adolescents (age: 14.9+/-0.4 years) were examined. Blood pressure, heart rate and EDA were continuously recorded during 6-min rest. Evaluated parameters were: low frequency band of systolic blood pressure variability, systolic, diastolic and mean blood pressure, mean RR interval, cardiac sympathetic indices: symbolic dynamics (0V%), left ventricular ejection time (LVET), pre-ejection period (PEP), and EDA. Our findings revealed significantly higher systolic, diastolic, and mean blood pressure values, shortened mean RR interval, increased 0V%, and shortened LVET in MVP patients vs. controls (p=0.028, p<0.001, p=0.002, p<0.001, p=0.050, p<0.001; respectively). Our study revealed enhanced cardiovascular sympathetic regulation in adolescent MVP patients. We suggest that evaluation of non-invasive sympathetic parameters could represent potential biomarkers for early diagnosis of cardiovascular complications associated with MVP already at adolescent age.
Keywords: Ventricular Function, Left; Male; galvanická kožní odpověď; sympatický nervový systém; funkce levé komory srdeční; Mitral Valve Prolapse; Adolescent; srdce; prognóza; Heart Rate; Age Factors; Case-Control Studies; mužské pohlaví; srdeční frekvence; mladiství; Galvanic Skin Response; lidé; krevní tlak; ženské pohlaví; studie případů a kontrol; Sympathetic Nervous System; mitrální insuficience; Humans; Blood Pressure; věkové faktory; Prognosis; prolaps mitrální chlopně; Female; Heart; Mitral Valve Insufficiency